Firearm use risk factors and access restriction among suicide decedents age 75 and older who disclosed their suicidal intent - Namkee G. Choi; C. Nathan Marti; Bryan Y. Choi (Frontiers Media S.A., 2023)
Background and aimsA majority of older adult suicide decedents used firearms. In this study, we focused on suicide decedents age 75+ who disclosed their suicidal intent within a month of their injury/death to examine demographic and clinical characteristics associated with firearm use and firearm access restriction attempts by their family members.MethodsThe 2017-2019 U.S. National Violent Death Reporting System provided data (N = 1,734 suicidal intent disclosers; 1,476 males and 258 females; 21.4% of decedents age 75+). Generalized linear model (GLM) for a Poisson distribution with a log link was used to examine firearm use risk factors. Firearm access restriction attempts by decedents' family members were examined based on coroner/medical examiner and law enforcement (CME/LE) reports.ResultsNearly three quarters of disclosers disclosed their intent to family members, and 82.9% of males and 27.5% of females used firearms. GLM results showed males, non-Hispanic white people, and residents in the South and West regions had higher likelihood of firearm use. CME/LE reports of 140 out of 1,294 firearm decedents included narratives related to firearm restriction attempts or lack thereof. Firearm access restrictions were not attempted in 65 cases because family members did not take suicidal intent disclosure seriously or because decedents promised no self-harm. Partial or complete removal of firearms in 75 cases were not effective as decedents had hidden a firearm or purchased a new one. Others used different lethal methods.ImplicationsThe findings indicate a need for: (a) training family members of older adults who are at risk of suicide in effective means safety/access restriction and strategies to prevent means substitution; (b) more comprehensive legislative reforms reducing access to firearms by those at risk of suicide; and (c) more comfort and palliative care and counseling for psychosocial risk factors.